Potency of Indian Shot (Canna indica) As Phytoremediator Physical Parameters of Water Quality in Supit Urang Fecal Waste Treatment Plant Malang City - Munawaroh, Ikhfini; Dwi Prasetyo, Hamdani; Latuconsina, Husain (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
Supit Urang Fecal Waste Treatment Plant (IPLT) is a facility provided in overcoming sanitation problems, the Supit Urang STP in addition to accommodating also treats fecal waste before being discharged into the river. In an effort to maximize the utilization of river water, it is necessary to monitor water according to quality standards. Water purification can be through filtration, adsorption, sedimentation, ion exchange and microbial processes using aquatic plants in wetland ponds. This study was conducted using observational descriptive by taking samples at the inlet, midpoint and outlet point. Sample testing was carried out at UNISMA Integrated Laboratory and Halal Center. The parameters observed are temperature, TDS, TSS Conductivity and turbidity. Then the value obtained from the observation will be compared with the quality standards set by the government. The effectiveness of the phytoremediation process using Indian Shot (Canna indica) is significantly able to reduce temperature, TDS, conductivity and turbidity parameters. In the TSS parameter, there was also a decrease even though the TSS value still exceeded the quality standard. The decrease and increase of the observed parameters is due to several factors both organic and inorganic factors of the waters. So this affects the phytoremediation process. The Constructed wetland method using Indian Shot (Canna indica) shows that all parameters decrease when the adsorption process by plant roots